Perbedaan Perencanaan Karier Ditinjau dari Tingkat Self Efficacy pada Mahasiswa Tingkat Akhir di Fakultas Kesehatan Dan Sains, Universitas Dhyana Pura - Ni Putu Dilla Pramestya Asih; Listiyani Dewi Hartika; I Gde Dhika Widarnandana (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2026)
This study was conducted at the Faculty of Health and Science, Dhyana Pura University with the aim of determining whether there are differences in career planning that can be seen from the level of self-efficacy in final year students. In this study used two measurement scales, namely the self-efficacy scale and the career planning scale. The sample in the study amounted to 96 which was determined using the Isaac and Michael formula. The method used in this study is comparative quantitative with data analysis using the Independent Sample T-Test test. The results of the Independent Sample T-Test obtained a p-value of 0.001 <0.05. Then, an additional analysis was conducted, namely the Post Hoc analysis test, obtained the result of Ptukey <0.001. Based on the results of the data analysis, it can be concluded that there are differences in career planning reviewed from the high and low levels of self-efficacy in final year students at the Faculty of Health and Science, Dhyana Pura University.